Implementation of Al-Quran Memorization Learning and the Habit of Fasting on Mondays and Thursdays in Forming Students' Religious Character - Silvia Vitaloka; Siti Nurdilah; Euis Fitriyani; Agus Supandi; Liwaul Hamdi; Adi Rosadi (Al-Alim: Jurnal Pendidikan Agama Islam, 2025)
This study discusses the implementation of Quran memorization and the habit of fasting on Mondays and Thursdays as strategies for building students' religious character at SDIT Unggulan Al-Barokah Madani Sukabumi. The main problem of this study focuses on the implementation process, obstacles, and impact of both programs in instilling Islamic values ​​contextually in an integrated Islamic elementary school. This study uses a qualitative approach with a case study method through observation, interviews, and documentation of teachers, students, and parents. The results show that the Tahfidz and fasting activities are implemented in a structured and sustainable manner with strong support from the school and active family involvement. The program has proven effective in fostering students' discipline, responsibility, and empathy through daily spiritual experiences. Despite obstacles such as differences in memorization abilities and fluctuations in motivation, teachers and parents are able to overcome them through a humanistic and collaborative approach. The conclusion of this study confirms that this religious practice-based learning contributes significantly to the formation of students' religious character and can be used as a model for the development of integrative Islamic education that combines habituation, role models, and sustainable family-school collaboration.